Analysis of Social Media Usage in Enhancing Communication and Collaboration in Educational Environments - Ripki, Ahmad Jauhari Hamid; Wulandari, Ayu; Arifannisa (Lembaga Intelektual Muda (LIM) Maluku, 2024)
In this rapidly evolving digital era, the use of social media has become an integral part of daily life, including among students, teachers, and parents in educational environments. This study aims to conduct an in-depth analysis of social media usage in efforts to enhance communication and collaboration in educational settings. The method employed in this research is a qualitative literature review utilizing data sourced from Google Scholar spanning from 2020 to 2024. Key search terms included social media, communication and collaboration, and education environment. The data analysis technique used in this research is qualitative data analysis. The qualitative data analysis process involves several steps, such as organising the data, forming themes or patterns, and interpreting the findings from the scientific articles used. The study's findings reveal that in the continuously evolving digital era, social media usage has become a crucial aspect across various domains, including education. The analysis of social media usage in enhancing communication and collaboration in educational environments highlights its significant potential to increase participant engagement, facilitate the exchange of ideas, and broaden the reach of educational information. However, the utilization of social media also necessitates a careful and responsible approach to address associated challenges and risks.